1994
DOI: 10.1002/aoc.590080406
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and excretion of arsenic compounds by a marine unicellular alga, polyphysa peniculus

Abstract: Polyphysa peniculus was grown in artificial seawater in the presence of arsenate, arsenite, monomethylarsonate and dimethylarsinic acid. The separation and identification of some of the arsenic species produced in the cells as well as in the growth medium were achieved by using hydride generation-gas chromatography-atomic absorption spectrometry methodology. Arsenite and dimethylarsinate were detected following incubation with arsenate. When the alga was treated with arsenite, dimethylarsinate was the major me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 39 publications
7
42
0
Order By: Relevance
“…We speculated that MMA was not present due to the speed of MMA transformation to DMA. Similar result has also been reported by Cullen et al (1994), when P.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We speculated that MMA was not present due to the speed of MMA transformation to DMA. Similar result has also been reported by Cullen et al (1994), when P.…”
Section: Discussionsupporting
confidence: 91%
“…Edmonds et al (1997) reported that when the unicellular microalga, Chaetoceros concavicornis was grown axenically in As(V) enriched water, oxoarsenosugar-sulfate (arsenosugar 4) was identified as the major As metabolite. Cullen et al (1994) cultured a unicellular microalga, Polyphysa peniculus, in artificial seawater with As(V) and As(III), and identified DMA as the major metabolic product in both the cells and the medium. However, little is known about whether marine microalgae can volatilize As and their potential contribution to the biogeochemical cycle of As.…”
Section: Introductionmentioning
confidence: 99%
“…Klumpp and Peterson (1981) claimed that the brown macroalga, Fucus spiralis, took up the arsenic as arsenate and transformed it into watersoluble organoarsenic compounds which were then further transformed into a lipid-soluble organoarasenic compound and 12 water-soluble organoarsenic compounds. Cullen et al (1994) found that Polyphysa peniculus transformed arsenate into arsenite and dimethylarsinate. However, few studies have been done on the transformation of arsenic in algae at different growth stages.…”
Section: Discussionmentioning
confidence: 99%
“…Few reports on the toxicity of arsenic species to Microcystis species have been documented, although studies on uptake and transformation of arsenic species by other phytoplankton have been performed [3,16,17]. In the present study, the inhibitory threshold concentration of As(III) to growth of M. aeruginosa FACHB 905 in culture was between 10 −5 and 10 −4 mol L −1 (Figure 1).…”
Section: Discussionmentioning
confidence: 45%